2020
DOI: 10.3389/fmed.2020.544412
|View full text |Cite
|
Sign up to set email alerts
|

18F-Fluorodeoxyglucose Positron Emission Tomography and Computed Tomography With Magnetic Resonance for Diagnosing Adult-Onset Still's Disease

Abstract: The objective of the study was to assess the advantages of 18 F-fluorodeoxyglucose (FDG) positron emission tomography and computed tomography with magnetic resonance (PET/CT-MR) in diagnosing and monitoring patients with adult-onset Still's disease (AOSD). Methods: Participants in this retrospective case-control study underwent whole-body 18 F-FDG-PET/CT-MR imaging. All PET scans were qualitatively and semiquantitatively analyzed using standardized uptake values (SUVs) normalized to liver uptake, i.e., we calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
(55 reference statements)
2
3
0
Order By: Relevance
“…PET/CT showed homogeneous and diffuse bone marrow hypermetabolism in 75% of the patients, confirming data from the main published studies, in which the bone marrow intensely fixed the marker in 80%–100% of cases [ 9 , 10 , 11 , 12 , 23 , 24 , 25 ]. This diffuse uptake is probably related to inflammatory parameters reflecting the cellular activation within the bone marrow [ 26 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…PET/CT showed homogeneous and diffuse bone marrow hypermetabolism in 75% of the patients, confirming data from the main published studies, in which the bone marrow intensely fixed the marker in 80%–100% of cases [ 9 , 10 , 11 , 12 , 23 , 24 , 25 ]. This diffuse uptake is probably related to inflammatory parameters reflecting the cellular activation within the bone marrow [ 26 ].…”
Section: Discussionsupporting
confidence: 84%
“…The examinations showed at least one hypermetabolic lymph node site at the same rate as in the published data (67–84% of cases) [ 9 , 11 , 12 , 24 , 25 ]. Hypermetabolic lymph nodes were preferentially supradiaphragmatic in our study.…”
Section: Discussionsupporting
confidence: 80%
“…Besides thediagnostic procedures mentioned in the recommendations, data also exist on the utility of procedures such as positron-emission tomography (PET) with or without computed tomography (PET-CT) [8,21,86,155,180], as well as on biopsies of liver [9], skin [64,96,116,120,131,167,214], mucous membranes [181], lymph nodes [84], and bone marrow [138], all of which may have a role in the differential diagnostic process of individual patients. Furthermore, multiple biomarkers other than ferritin or IL-18 have been assessed [16, 19, 30, 32-38, 38-41, 43, 45, 68, 74-76, 79, 88, 95, 101, 102, 104, 108, 135, 160, 161, 186, 188, 197], but validation studies are largely lacking.…”
Section: Discussionmentioning
confidence: 99%
“…X-rays or ultrasounds have proven to be unhelpful in the diagnostic process and no radiological criteria for AOSD exist. However, it was reported that the employment of 18 F-fluoro-2-deoxyglucose ( 18 F-FDG) positron emission tomography (PET) with computed tomography (CT) or magnetic resonance (MR) may support AOSD diagnosis and response to therapy [ 77 ]. Although a specific uptake cannot be detected and the differential diagnosis with haematological malignancies is mandatory, subjects with AOSD usually present with higher 18 F-FDG uptake than non-AOSD in specific areas, namely bone marrow, spleen and lymph nodes [ 77 ].…”
Section: Supporting Diagnosis: Old and New Biomarkers And The Role Of...mentioning
confidence: 99%
“…However, it was reported that the employment of 18 F-fluoro-2-deoxyglucose ( 18 F-FDG) positron emission tomography (PET) with computed tomography (CT) or magnetic resonance (MR) may support AOSD diagnosis and response to therapy [ 77 ]. Although a specific uptake cannot be detected and the differential diagnosis with haematological malignancies is mandatory, subjects with AOSD usually present with higher 18 F-FDG uptake than non-AOSD in specific areas, namely bone marrow, spleen and lymph nodes [ 77 ]. The qualitative analysis, usually performed by an expert nuclear medicine radiologist, is essential for detecting active areas, whereas the quantitative analysis, through the assessment of standardised uptake values (SUVs), is important to establishing and quantifying hypermetabolic areas.…”
Section: Supporting Diagnosis: Old and New Biomarkers And The Role Of...mentioning
confidence: 99%